IMPROVING CRITICAL READING ABILITY, LEARNING AUTONOMY, AND LEARNING PARTICIPATION THROUGH KAHOOT! APPLICATION - Yusti Arini; Ika Sulistyarini (UIN Raden Mas Said Surakarta, 2021)
This research is aimed at finding out whether the use of Kahoot! application can increase the students’ critical reading ability, learning autonomy, and their learning participation in Critical Reading learning process. This research was conducted at the English Education Program Study of IAIN Surakarta involving 36 students as the research subjects. This classroom action research consisted of 2 cycles; 5 meetings for each cycle, with 1 pre-test and 2 post-tests. Based on the research results, it can be found out that the mean of pre-test scores is 25.56, the mean of post-test 1 is 44.39, and the mean of post-test 2 is 66.17; it means that the use of Kahoot! application can increase the students’ critical reading ability. The results of the questionnaire consisting of 9 indicators show that the use of Kahoot! application can increase the students’ learning autonomy. Furthermore, results from observation also show that the students’ learning participation increased during the learning process when Kahoot! application was applied. The students also assumed that the use of Kahoot! application can increase their learning participation.